Folkcomunicação, ciências sociais e estudos folclóricos : entrelaçamento e embates - Ramos, Tiago Roberto (2014)
This dissertation studies the relationship between the theory of folk communication, formulated in the 1960s by Luis Beltran de Andrade e Lima, the Social Sciences and Folcklore Studies. All these traditions were in folklore a universe for reflection. The objective is to understand the intersections, interactions , entanglements and clashes between folk communication, Social Sciences and Folklore Studies, reporting and describing the characteristics of this exchange. Here, we question the kind of relationship that folk communication established with the Social Sciences and Folklore Studies. Wright Mills (2009) and his conception of intellectual craftsmanship is the origin of our methodology. It is from their reflections that developed the research literature and qualitative. Analytically, we mobilize different methodological perspectives. Pierre Bourdieu (1983) helps us to understand the logic of the structure and workings of the scientific field. Raymond Williams (1999) provides an explanation of the forms of scientific values between different intellectual groups sharing. Heloise Pontes (1991, 1997, 1998), in turn, helps in developing a sociology of intellectual production and its producers. Text, author, social and institutional context were the main analytical and explanatory criteria employed. Each of these criteria showed a characteristic of the relationship studied. In terms of copyright, Luis Beltrão is in the same generation platform that leading intellectuals of Social Sciences and Folklore Studies. Regarding the text, analyzing his doctoral thesis, is perceived a strong influence of sociological and folkloric thought of the period. As social and institutional context, Beltrão had the project of scientific quest for autonomy in communication studies. During this period, social science and folklore studies also strove for the conquest of scientific autonomy. The folkcommunication, while theoretical elaboration, had the ability to express the dilemmas of institutionalization of Communication in